O impacto da relação de troca entre o líder e seus liderados na comunicação de sua equipe - Soares, Eduardo Dantas (2018)
The leader's relationship with its members has been much studied by academics around the world. Despite all these efforts, I identified in my research that the intensity of the leader's communication with his followers and the intensity of communication among followers had not been sufficiently explored to explain how such communication could emerge in a business team. To identify the particularities of the communication of a team and its leader, I investigated twelve organizational teams of small family businesses in the State of São Paulo. The objective of this study was to test a theoretical model that could explain how the evaluation of the team on the leader could influence the communication of this team with the leader. I sought to achieve this objective and make the study more specific by having the teams respond to a questionnaire about their demographic particulars, the virtual and face-to-face amounts of communications, among all team members, their level of organizational involvement, and how the leader is judged by the exchange ratio between the team members and your leader. The results of the research were obtained through the use of the Partitional Last Square (PLS) tool. As main results I identified that the communication between the members of the company mediates the communication between the leader and his followers. Organizational involvement has been confirmed as an antecedent of the exchange relationship between the team members and the leader.